MEMAHAMI KONSEP BALANCED SCORECARD - Anna Probowati (FE Program Studi Manajemen, 2006)
Balanced scorecard is one of strategic planning method in strategic management system which is used as a tool for managing strategic implementation, to measure performance entirely, to communicate vission, strategic, and goal among the stakeholders in organization. In emphasizing for “balanced”, balanced scorecard uses four perspective to determine the strategic goals: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Keywords: balanced scorecard, strategic management system, four perspective